Peran Sektor Keuangan Perbankan Dalam Mengatasi Kemiskinan Di Indonesia - Clinton Sinaga; Berdin Rumahhorbo; Angry Sitanggang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the role of the financial sector in poverty alleviation in Indonesia using annual data for the period 1980-2014. The ARDL cointegration approach is used to show the existence of a long-run trade-off between the financial sector and poverty alleviation. In addition, the Granger causality VECM method is also used to detect the direction of the causal relationship between the financial sector and poverty. In addition, to measure the time horizon and relative intensity of poverty in response to shocks experienced by the financial sector, impulse response functions (IRF) and variance decomposition (VDC) are used. Private sector money supply and domestic credit ratio are used as indicators of financial sector development, while poverty is measured by household consumption expenditure per capita and economic growth is measured by gross domestic product (GDP) per capita. The results show that there is a long-run relationship between the financial sector, economic growth and poverty alleviation in Indonesia. Furthermore, the results show that there is a two-way causal relationship between the financial sector and poverty. The contribution of money supply and private credit ratio to poverty shocks is positive. Therefore, to accelerate poverty alleviation, the government can adopt a policy that requires commercial banks to provide convenient lending conditions for the poor and the private sector.